Lithium metal anode with crystal plane preferred orientation, preparation method and battery

CN123017867APending Publication Date: 2026-10-30SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611304940.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

CN118888819A公开了一种超薄锂箔的电化学制备方法,通过电沉积降低超薄锂箔的厚度,得到厚度均匀的超薄锂箔;CN108346778A公开了一种制备超薄锂金属负极的电化学方法,通过调节电沉积时间和电流密度来调整超薄锂金属负极的厚度,但现有技术在锂金属负极制备的电沉积过程中易出现锂枝晶和不均匀锂沉积,且未对沉积后锂金属的晶面取向进行系统性调控和强化,所获得的晶面一致性不足、沉积层与铜箔基底的界面结合状态也尚未被关注和优化

Benefits of technology

(1)实现了具有{110}晶面择优取向的锂金属负极的快速制备。本申请通过电沉积与辊压后处理相结合,在电沉积所用电解液中加入添加剂并调控其含量,抑制大电流密度电沉积时的锂枝晶生长和不均匀锂沉积,并结合辊压后处理抑制非{110}晶面的锂沉积,促进{110}晶面的择优取向生长,制备得到平整超薄且晶面取向一致的锂金属负极材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017867A_ABST
    Figure CN123017867A_ABST
Patent Text Reader

Abstract

The application relates to a lithium metal negative electrode with crystal face preferred orientation, a preparation method and a battery. The preparation method comprises sequentially performing electrodeposition and post-rolling treatment, the composition of an electrolyte used in the electrodeposition comprises a lithium salt, an organic solvent and an additive; the additive comprises lithium nitrate; the content of the additive in the electrolyte is 0.05wt%-0.5wt%; the current density of the electrodeposition is 5mA / cm 2 Above. The application combines electrodeposition and post-rolling treatment, adds an additive in the electrolyte used in the electrodeposition and regulates the content of the additive, inhibits lithium dendrite growth and non-uniform lithium deposition in large current density electrodeposition, and combines post-rolling treatment to inhibit lithium deposition on non-{110} crystal faces, promote {110} crystal face preferred orientation growth, prepare a smooth and ultrathin lithium metal negative electrode material with consistent crystal face orientation, and the symmetrical battery assembled from the prepared lithium metal negative electrode has good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of lithium battery technology, specifically relating to a method for preparing a lithium metal anode, and more particularly to a lithium metal anode with preferred crystal orientation, a preparation method thereof, and a battery thereof. Background Technology

[0002] Lithium metal anodes are considered one of the most promising anode materials for next-generation high-energy-density rechargeable batteries due to their extremely high theoretical specific capacity (3860 mAh / g) and the lowest electrochemical potential (-3.04 V vs. SHE). However, lithium metal anodes suffer from problems such as lithium dendrite growth, volume expansion, and severe interfacial side reactions during charge-discharge cycling, which seriously restrict their commercial application. Currently, the main preparation processes for lithium metal anodes include extrusion rolling, melt coating, thermal evaporation / sputtering deposition, and electrodeposition.

[0003] The most widely used method for industrial production of lithium metal anodes is the extrusion rolling process. This process thins bulk lithium metal to the desired thickness through repeated mechanical rolling. However, when the target thickness is below 20 μm, the difficulty of the process increases exponentially due to the soft texture and low tensile strength of lithium metal, leading to a significant decrease in yield. To prepare ultra-thin lithium foil, auxiliary substances such as lubricating oil are often used in production, but these impurities remaining on the lithium metal surface can severely degrade battery performance. Furthermore, repeated rolling operations exacerbate oxidation on the lithium metal surface and introduce uneven oxide impurities. From a microstructural perspective, lithium metal anodes produced by this process often have disordered crystal orientations, typically exhibiting both {110} and {200} crystal planes simultaneously, making it difficult to control the preferred orientation of these planes.

[0004] The melt coating method involves heating lithium metal to above its melting point (180.5℃), spreading the molten lithium onto a substrate, and then cooling it to form a solid shape. Due to the high surface tension of molten lithium metal, it is difficult to achieve uniform spreading of the molten lithium metal during the preparation process, and the thickness of the lithium metal is difficult to control precisely. Currently, this method is only at the laboratory stage and is difficult to scale up for production. The thermal evaporation / sputtering deposition method deposits a thin film of lithium metal on a substrate under vacuum conditions through physical vapor deposition. This method can precisely control the deposition thickness, but it requires huge equipment investment, has extremely low production efficiency, and high process costs, which cannot meet the needs of large-scale industrial production.

[0005] Existing electrodeposition methods mainly involve depositing lithium metal onto copper foil. CN118888819A discloses an electrochemical method for preparing ultrathin lithium foil, which reduces the thickness of the ultrathin lithium foil through electrodeposition to obtain a uniformly thick ultrathin lithium foil. CN108346778A discloses an electrochemical method for preparing ultrathin lithium metal anodes, which adjusts the thickness of the ultrathin lithium metal anode by adjusting the electrodeposition time and current density. However, existing technologies are prone to lithium dendrites and uneven lithium deposition during the electrodeposition process of lithium metal anode preparation. Furthermore, the crystal orientation of the deposited lithium metal is not systematically controlled and strengthened, resulting in insufficient crystal uniformity. The interfacial bonding state between the deposited layer and the copper foil substrate has also not been addressed or optimized.

[0006] Existing technologies struggle to simultaneously achieve ultrathinness, uniform crystal orientation (concentration of the {110} crystal plane), and rapid, scalable production. Furthermore, those skilled in the art have long overlooked the decisive influence of the initial crystal orientation of lithium metal anodes on the uniformity of lithium deposition during subsequent cycles, and no technical solution has yet been found to efficiently and cost-effectively prepare ultrathin lithium metal anodes with highly uniform crystal orientation.

[0007] Therefore, how to prepare and mass-produce ultrathin lithium metal anodes with {110} crystal orientation has become an urgent problem to be solved. Summary of the Invention

[0008] To address the shortcomings of existing technologies, the purpose of this application is to provide a lithium metal anode with preferred crystal orientation, a preparation method, and a battery. The preparation method provided in this application involves electrodeposition combined with a rolling post-processing step. Additives are added to the electrolyte used for electrodeposition, and their content is controlled to ensure that the resulting lithium metal anode material is flat, ultra-thin, and has consistent crystal orientation.

[0009] To achieve this objective, the present application adopts the following technical solution: In a first aspect, this application provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequentially performing electrodeposition and rolling post-processing, wherein the electrolyte used for electrodeposition comprises lithium salt, organic solvent and additives. The additive includes lithium nitrate; The additive content in the electrolyte is 0.05wt% to 0.5wt%, for example, it can be 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt% or 0.5wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0010] The current density of the electrodeposition is 5 mA / cm². 2 For example, it could be 5mA / cm 27mA / cm 2 9mA / cm 2 11mA / cm 2 13mA / cm 2 15mA / cm 2 17mA / cm 2 19mA / cm 2 Or 21mA / cm 2 This applies to, but is not limited to, the listed values; other unlisted values ​​within the range are also applicable.

[0011] This application combines electrodeposition and roll pressing post-treatment. By adding additives to the electrolyte used for electrodeposition and adjusting their content, lithium dendrite growth and uneven lithium deposition are suppressed during high current density electrodeposition. Combined with roll pressing post-treatment, lithium deposition on non-{110} crystal planes is suppressed, and the preferred orientation growth of {110} crystal planes is promoted, thus preparing a flat, ultrathin lithium metal anode material with consistent crystal orientation.

[0012] In some embodiments, the preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent and additives; (2) In a protective atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode.

[0013] In some embodiments, the lithium salt in the electrolyte of step (1) includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, or lithium bis(fluorosulfonyl)imide.

[0014] In some embodiments, the lithium salt concentration in the electrolyte in step (1) is 0.5 mol / L to 2.0 mol / L, for example, it can be 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2.0 mol / L, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0015] In some embodiments, the organic solvent in the electrolyte of step (1) includes carbonate solvents and / or ether solvents.

[0016] In some embodiments, the electrolyte in step (1) further includes auxiliary additives.

[0017] In some embodiments, the carbonate solvent in the organic solvent of step (1) includes at least one of ethylene carbonate, diethyl carbonate, or dimethyl carbonate.

[0018] In some embodiments, the ether solvent in the organic solvent of step (1) includes at least one of 1,3-dioxolane or ethylene glycol dimethyl ether.

[0019] In some embodiments, the auxiliary additives in the electrolyte include cesium hexafluorophosphate.

[0020] In some embodiments, the content of the auxiliary additive in the electrolyte is 0.01wt% to 0.1wt%, for example, it may be 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt% or 0.1wt%, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0021] In some embodiments, the working electrode in step (2) comprises copper foil.

[0022] In some embodiments, the thickness of the working electrode in step (2) is 6μm to 20μm, for example, it can be 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm or 20μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0023] In some embodiments, the surface roughness Ra of the working electrode in step (2) is less than 1 μm, for example, it can be 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0024] In some embodiments, the protective atmosphere used in step (2) includes nitrogen and / or an inert gas, wherein the inert gas includes at least one of helium, neon or argon.

[0025] In some embodiments, the electrodeposition method in step (2) includes constant current electrodeposition.

[0026] In some embodiments, the deposition capacity of the electrodeposition in step (2) is 2 mA·h / cm². 2 ~5mA·h / cm 2 For example, it could be 2mA·h / cm 2 2.5 mA·h / cm 2 3mA·h / cm 2 3.5 mA·h / cm 2 4mA·h / cm 2 4.5 mA·h / cm 2 Or 5mA·h / cm2 However, this does not apply to all values ​​listed, but rather to other unlisted values ​​within the range.

[0027] In some embodiments, the current density of electrodeposition in step (2) is 5 mA / cm². 2 ~20mA / cm 2 .

[0028] In some embodiments, the post-rolling treatment in step (3) includes at least one post-rolling treatment.

[0029] In some embodiments, the rolling temperature of the post-rolling treatment in step (3) is 20°C to 40°C, for example, it can be 20°C, 25°C, 30°C, 35°C or 40°C, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0030] In some embodiments, the rolling speed of the post-rolling treatment in step (3) is 5m / min to 50m / min, for example, it can be 5m / min, 10m / min, 15m / min, 20m / min, 25m / min, 30m / min, 35m / min, 40m / min, 45m / min or 50m / min, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0031] In some embodiments, the rolling pressure of the post-rolling treatment in step (3) is 50MPa to 200MPa, for example, it can be 50MPa, 60MPa, 70MPa, 80MPa, 90MPa, 100MPa, 120MPa, 140MPa, 160MPa, 180MPa or 200MPa, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0032] In some embodiments, after the roll pressing process described in step (3), the roll is annealed in an inert atmosphere at a temperature of 60°C to 100°C for a time of 10 min to 60 min.

[0033] The annealing temperature is 60℃~100℃, for example, it can be 60℃, 70℃, 80℃, 90℃ or 100℃, but is not limited to the listed values. Other values ​​within the range that are not listed are also applicable.

[0034] Annealing time is 10 min to 60 min, for example, it can be 10 min, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values. Other values ​​not listed within the range are also applicable.

[0035] Secondly, this application provides a lithium metal anode with preferred crystal orientation prepared by the preparation method described in the first aspect.

[0036] The thickness of the lithium metal anode is 10μm to 25μm, for example, it can be 10μm, 11μm, 13μm, 15μm, 17μm, 19μm, 21μm, 23μm or 25μm, but is not limited to the listed values. Other unlisted values ​​within the range are also applicable.

[0037] The preferred orientation of the lithium metal anode is the {110} crystal plane.

[0038] Thirdly, this application provides a battery, wherein the negative electrode of the battery comprises a lithium metal negative electrode with preferred crystal orientation prepared by the preparation method described in the first aspect, or comprises a lithium metal negative electrode with preferred crystal orientation as described in the second aspect.

[0039] The numerical range described in this application includes not only the point values ​​listed above, but also any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of brevity, this application will not exhaustively list the specific point values ​​included in the range.

[0040] Compared with the prior art, this application has the following advantages: (1) Rapid preparation of lithium metal anodes with preferred {110} crystal orientation has been achieved. This application combines electrodeposition with roll pressing post-processing. Additives are added to the electrolyte used for electrodeposition and their content is controlled to suppress lithium dendrite growth and uneven lithium deposition during high current density electrodeposition. Combined with roll pressing post-processing, lithium deposition of non-{110} crystal planes is suppressed, and preferred orientation growth of {110} crystal planes is promoted, thus preparing a flat, ultrathin lithium metal anode material with consistent crystal orientation.

[0041] (2) Ultrathin preparation has been achieved. This application uses electrodeposition to precisely control the deposition capacity, which enables the stable preparation of ultrathin lithium metal anodes with a thickness of 10~25μm. This is far superior to the problem of exponentially increasing process difficulty faced by the existing extrusion rolling method when making ultrathin anodes. Attached Figure Description

[0042] Figure 1 This is a schematic flowchart of the preparation method of lithium metal anode with preferred crystal orientation provided in Examples 1 to 11 of this application.

[0043] Figure 2 This is a photograph of the lithium metal anode obtained in Example 1 of this application.

[0044] Figure 3 This is a SEM image of the lithium metal anode before rolling in Example 1 of this application.

[0045] Figure 4 This is a SEM image of the lithium metal negative electrode after rolling in Example 1 of this application.

[0046] Figure 5 This is an XRD analysis of the lithium metal anodes obtained in Example 1 and Comparative Example 2 of this application.

[0047] Figure 6 This is an analysis of the XRD results of the lithium metal anode before and after rolling in Example 1 of this application.

[0048] Figure 7 This is the surface chemical XPS analysis of the lithium metal anode obtained in Example 1 of this application.

[0049] Figure 8 XPS analysis of the surface chemistry of the lithium metal anode obtained in Comparative Example 1 of this application.

[0050] Figure 9 This is a performance analysis of the symmetrical battery assembled with lithium metal anodes obtained in Example 1 and Comparative Example 1 of this application. Detailed Implementation

[0051] The technical solution of this application will be further described below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely to help understand this application and should not be regarded as specific limitations on this application.

[0052] The "range" disclosed in this application can be defined in the form of a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints. Any endpoint can be independently included or excluded, and they can be combined arbitrarily; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are also listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0" and "5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥2, it is equivalent to listing integers such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For instance, when a parameter is described as an integer selected from "2~10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0053] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0054] The term "embodiment" as used in this application means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments.

[0055] Those skilled in the art will understand that the order in which the steps are written in the methods of the various embodiments does not imply a strict execution order. The detailed execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps of this application may be performed sequentially or randomly, but are preferably performed sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), meaning that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0056] In this application, open-ended technical features or solutions described with terms such as "comprising" do not exclude additional members beyond those listed unless otherwise specified. They can be considered as providing both closed-ended features or solutions comprised of the listed members and open-ended features or solutions that include additional members beyond the listed members. For example, if A includes a1, a2, and a3, it may also include other members or exclude additional members unless otherwise specified. This can be considered as providing both technical features or solutions where "A consists of a1, a2, and a3" or "A is selected from a1, a2, and a3," and technical features or solutions where "A includes not only a1, a2, and a3, but also other members."

[0057] In this application, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" represents a group consisting of A, B, and "a combination of A and B". "Containing A and / or B" can mean "containing A, containing B, and containing A and B", or "containing A, containing B, or containing A and B", and can be appropriately understood according to the context.

[0058] In this application, the terms "first aspect," "second aspect," "third aspect," "fourth aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first," "second," "third," "fourth," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.

[0059] Example 1 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, and the process flow diagram is shown below. Figure 1 As shown, the preparation method includes sequential electrodeposition and roll pressing post-treatment; The electrolyte used for electrodeposition comprises lithium salt (lithium bis(trifluoromethanesulfonylimide)), organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0060] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium bis(trifluoromethanesulfonylimide) was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate and CsPF₆ were then added to the above basic electrolyte at amounts of 0.2 wt% and 0.05 wt% of the total electrolyte mass, respectively, and stirred until completely dissolved to obtain the electrolyte.

[0061] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density of 5 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 60 min (5 mA·h / cm). 2 ÷5mA / cm 2 =1h=60min).

[0062] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0063] Figure 2 The image shows a photograph of the lithium metal anode prepared in this embodiment. It can be seen that the obtained lithium metal anode has a smooth surface and a small thickness. Figure 3 and Figure 4 These are SEM images of the lithium metal anode before and after rolling in step (3) of this embodiment. It can be seen that the surface of the lithium metal anode after rolling is flat and without pores. Figure 6 The XRD results analysis of the lithium metal anode before and after rolling in step (3) of this embodiment shows that the lithium metal anode after rolling has a better Li{110} crystal orientation. Figure 7 The surface chemical XPS analysis of the lithium metal anode prepared in this embodiment shows that no impurities were introduced after a single rolling process.

[0064] Example 2 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium hexafluorophosphate), organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.05 wt%.

[0065] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium hexafluorophosphate was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 0.5 mol / L. Lithium nitrate and CsPF₆ were then added to the basic electrolyte at amounts of 0.05 wt% and 0.01 wt% of the total electrolyte mass, respectively. The mixture was stirred until completely dissolved to obtain the final electrolyte.

[0066] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density set to 10 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 30 min (5 mA·h / cm). 2 ÷10mA / cm 2 =0.5h=30min).

[0067] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 60°C for 10 minutes.

[0068] Example 3 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium bis(fluorosulfonyl)imide), organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.5 wt%.

[0069] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium difluorosulfonylimide was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 2 mol / L. Lithium nitrate and CsPF₆ were then added to the basic electrolyte at amounts of 0.5 wt% and 0.1 wt% of the total electrolyte mass, respectively, and stirred until completely dissolved to obtain the final electrolyte.

[0070] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density set to 20 mA / cm². 2 The deposition capacity is 4 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 12 min (4 mA·h / cm). 2 ÷20mA / cm 2 =0.2h=12min).

[0071] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 100°C for 60 minutes.

[0072] Example 4 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises a lithium salt (lithium bis(trifluoromethanesulfonylimide)), an organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), and additives. The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0073] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent and additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium bis(trifluoromethanesulfonylimide) was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate (0.2 wt% of the total electrolyte mass) was then added to the basic electrolyte and stirred until completely dissolved to obtain the final electrolyte.

[0074] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density of 5 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 60 minutes.

[0075] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0076] In this embodiment, except that no auxiliary additives were added, everything else is the same as in Example 1.

[0077] Example 5 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium bis(trifluoromethanesulfonylimide)), organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0078] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium bis(trifluoromethanesulfonylimide) was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate and CsPF₆ were then added to the above basic electrolyte at amounts of 0.2 wt% and 0.05 wt% of the total electrolyte mass, respectively, and stirred until completely dissolved to obtain the electrolyte.

[0079] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density set to 25 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 12 minutes.

[0080] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0081] In this embodiment, except for the current density which is different from that in Example 1, everything else is the same as in Example 1.

[0082] Example 6 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium bis(trifluoromethanesulfonylimide)), organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0083] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium bis(trifluoromethanesulfonylimide) was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate and CsPF₆ were then added to the above basic electrolyte at amounts of 0.2 wt% and 0.05 wt% of the total electrolyte mass, respectively, and stirred until completely dissolved to obtain the electrolyte.

[0084] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density of 5 mA / cm². 2 The deposition capacity is 2 mA·h / cm³. 2Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 24 minutes.

[0085] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0086] In this embodiment, except for the deposition capacity, everything else is the same as in Example 1.

[0087] Example 7 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium bis(trifluoromethanesulfonylimide)), organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0088] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium bis(trifluoromethanesulfonylimide) was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate and CsPF₆ were then added to the above basic electrolyte at amounts of 0.2 wt% and 0.05 wt% of the total electrolyte mass, respectively, and stirred until completely dissolved to obtain the electrolyte.

[0089] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density of 5 mA / cm². 2 The deposition capacity is 3 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 36 minutes.

[0090] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0091] In this embodiment, except for the deposition capacity, everything else is the same as in Example 1.

[0092] Example 8 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium bis(trifluoromethanesulfonyl)imide), organic solvent (ethylene carbonate and diethyl carbonate), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0093] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), lithium bis(trifluoromethanesulfonyl)imide was dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate and CsPF6 were then added to the above basic electrolyte at amounts of 0.2 wt% and 0.05 wt% of the total electrolyte mass, respectively, and stirred until completely dissolved to obtain the electrolyte.

[0094] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density of 5 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 60 minutes.

[0095] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0096] In this embodiment, except for the organic solvent, everything else is the same as in Example 1.

[0097] Example 9 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium bis(trifluoromethanesulfonylimide)), organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), additives and auxiliary additives (CsPF6). The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0098] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent, additives and auxiliary additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium bis(trifluoromethanesulfonylimide) was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate and CsPF₆ were then added to the above basic electrolyte at amounts of 0.2 wt% and 0.05 wt% of the total electrolyte mass, respectively, and stirred until completely dissolved to obtain the electrolyte.

[0099] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density of 5 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 60 minutes.

[0100] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa.

[0101] In this embodiment, except that no annealing treatment was performed after rolling, everything else is the same as in Example 1.

[0102] Example 10 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises a lithium salt (lithium bis(trifluoromethanesulfonylimide)), an organic solvent (1,3-dioxolane and ethylene glycol dimethyl ether), and additives. The additive is lithium nitrate, and its content in the electrolyte is 0.2 wt%.

[0103] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent and additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium bis(trifluoromethanesulfonylimide) was dissolved in a mixed solvent of 1,3-dioxolane and ethylene glycol dimethyl ether in a 1:1 volume ratio to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate (0.2 wt% of the total electrolyte mass) was then added to the basic electrolyte and stirred until completely dissolved to obtain the final electrolyte.

[0104] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density set to 10 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 30 minutes.

[0105] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0106] In this embodiment, except that no auxiliary additives were added and the current density is different from that in Example 1, everything else is the same as in Example 1.

[0107] Example 11 This embodiment provides a method for preparing a lithium metal anode with preferred crystal orientation, the method comprising sequential electrodeposition and roll forming post-processing; The electrolyte used for electrodeposition comprises lithium salt (lithium hexafluorophosphate), organic solvent (ethylene carbonate and diethyl carbonate), and additives. The additive is lithium nitrate, and its content in the electrolyte is 0.1 wt%.

[0108] The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent and additives; In an argon glove box (H₂O < 0.1 ppm, O₂ < 0.1 ppm), lithium hexafluorophosphate was dissolved in a mixed solvent of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1 to prepare a basic electrolyte with a lithium salt concentration of 1.0 mol / L. Lithium nitrate (0.1 wt% of the total electrolyte mass) was then added to the basic electrolyte and stirred until completely dissolved to obtain the final electrolyte.

[0109] (2) In an argon atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. A rolled copper foil with a thickness of 12 μm and a surface roughness Ra≤0.5 μm was used as the working electrode, and a lithium metal sheet was used as the counter electrode. The copper foil was ultrasonically cleaned in acetone, ethanol and deionized water for 10 min each, and then dried in a vacuum drying oven at 60 °C for 2 h. The dried copper foil was then transferred to an argon glove box. In an argon-filled glove box, copper foil and lithium sheet were immersed in the electrolyte prepared in step (1). The effective deposition area of ​​the copper foil was 2 cm × 2 cm. Constant current electrodeposition was used, with a current density of 5 mA / cm². 2 The deposition capacity is 5 mA·h / cm³. 2 Electrodeposition was performed at room temperature (25°C) without stirring the electrolyte. After electrodeposition, the copper foil with deposited lithium metal was removed from the electrolyte, rinsed three times with ethylene glycol dimethyl ether solvent to remove residual electrolyte, and then allowed to air dry at room temperature. The electrodeposition time was approximately 60 minutes.

[0110] (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode; The composite obtained in step (2) was placed at room temperature (25°C) and subjected to a single roll pressing process using a precision roll press. The roll pressing linear speed was set to 10 m / min and the roll pressing pressure was set to 100 MPa. After rolling, the resulting lithium metal anode is annealed in an inert atmosphere at a temperature of 80°C for 30 minutes.

[0111] In this embodiment, except for the types of lithium salt and organic solvent, the content of additives, and the absence of auxiliary additives, everything else is the same as in Example 1.

[0112] Comparative Example 1 This comparative example provides a method for preparing a lithium metal anode, using a commercial extrusion rolling process to prepare a 25 μm thick lithium metal anode (MF-Li). The bulk lithium metal is thinned by at least two repeated rolling processes at room temperature, and then bonded to a 12 μm copper foil during the final rolling process.

[0113] Figure 8 The XPS results of this comparative example show that, due to the use of lubricant, the lithium metal anode obtained by repeated rolling introduces silicon-containing impurities. Figure 9 This is a performance comparison of the symmetrical batteries assembled with lithium metal anodes obtained in Example 1 and this comparative example. It can be seen that Example 1 has good cycle performance, while the cycle life of this comparative example is low.

[0114] Comparative Example 2 This comparative example provides a method for preparing a lithium metal anode. Except for the composition of the electrolyte, which is different from that in Example 1, everything else is the same as in Example 1.

[0115] No additives or auxiliary additives were added to the electrolyte used in this comparative example.

[0116] Figure 5 The comparison of the XRD results of the lithium metal anode obtained in Example 1 and this comparative example shows that the lithium metal anode prepared with electrolyte without additives and auxiliary additives has lower diffraction peak intensity and poorer crystal plane uniformity than that in Example 1.

[0117] Comparative Example 3 This comparative example provides a method for preparing a lithium metal anode. Except for the electrodeposition current density, which is different from that in Example 1, the method is the same as that in Example 1.

[0118] In this comparative example, the electrodeposition current density is 1 mA / cm². 2 .

[0119] Test Example 1 The lithium metal anodes obtained in Examples 1 to 11 and Comparative Examples 1 to 3 were characterized by XRD and SEM, and the lithium metal anodes were assembled into symmetrical cells for cycle performance testing.

[0120] Performance testing includes the following steps: (1) Symmetrical battery assembly: The lithium anode materials provided in all the embodiments and comparative examples are used as the positive and negative electrodes of the coin cell, and the Celgard2032 separator is used to assemble them into symmetrical cells; (2) Cyclic performance test: The charge / discharge current density was set to 1 mA cm⁻¹. -2 The test temperature was 30℃, and the charge and discharge time was 1 hour each to evaluate the number of stable cycles of the symmetrical battery.

[0121] The test results of the above embodiments and comparative examples are summarized in the table below: Table 1 It should be noted that, due to the low intensity of the diffraction peak of the Li{200} crystal plane, Li{110} / Cu{200} is selected in Table 1 to characterize the crystal plane orientation of the lithium metal anode. The higher the Li{110} / Cu{200} ratio, the more consistent the crystal plane orientation of the lithium metal anode.

[0122] Based on the above test results, it can be seen that: (1) As can be seen from Examples 1 to 11 and Comparative Examples 1 and 2, by combining electrodeposition and rolling post-treatment and adding additives to the electrolyte, the prepared lithium metal anode has a smooth and dense surface, consistent Li{110} crystal orientation, and Li{110} / Cu{200} ratio of 0.879 to 1.367. When assembled into a symmetrical battery for cycle performance testing, its cycle performance is better than that of Comparative Examples 1 and 2. Comparative Example 1, due to the use of only mechanical rolling, has only a weak signal at Li{110} and obvious strong diffraction peaks at Cu{200}, with disordered crystal orientation. XPS and TOF-SIMS analyses showed that Comparative Example 1 had a thicker oxide corrosion layer on its surface and contained Si element signals, which originated from the silicon-containing lubricant used in the rolling process, resulting in uneven surface composition. Comparative Example 2, due to the absence of additives and auxiliary additives in the electrolyte, had a lithium metal anode with poorer surface smoothness, crystal orientation, and cycle performance of symmetrical cells compared to Example 1.

[0123] (2) Examples 1 and 4 investigated the effect of auxiliary additives on lithium metal anodes prepared by electrodeposition combined with roll pressing post-treatment. The results showed that the addition of auxiliary additives further refined the deposited grains, making the lithium metal deposition layer more uniform and dense, and improving the surface smoothness. Examples 1 and 5, and Comparative Example 3 investigated the effect of current density on lithium metal anodes prepared by electrodeposition combined with roll pressing post-treatment. The results showed that the current density at 5 mA / cm² was optimal. 2 ~20mA / cm 2 Within a certain range, the orientation of the lithium metal anode crystal plane is more concentrated. When the current density is too low, the uniformity of the lithium deposition crystal plane decreases; when the current density is too high, the lithium deposition process becomes unstable, affecting the flatness of the lithium deposition.

[0124] (3) Examples 1, 6, and 7 investigated the effect of deposition capacity on lithium metal anodes prepared by electrodeposition combined with rolling post-processing. The results showed that when the deposition capacity was 2 mA·h / cm 2 ~5mA·h / cm 2 Within the specified range, the thickness of the obtained lithium metal anode is 10μm~25μm, and the crystal orientation is consistent. As the deposition capacity increases, the thickness of the lithium metal anode increases, and the cycle life is improved. Examples 1 and 8 investigated the effect of organic solvents on the preparation of lithium metal anodes. The results showed that the lithium metal grain size deposited in the carbonate system is slightly larger and the surface roughness is slightly higher. The lithium metal anode obtained in the ether system has a smaller grain size, more uniform lithium deposition, and better surface smoothness.

[0125] (4) Examples 1 and 9 investigated the effect of annealing after rolling on the prepared lithium metal anode. The internal stress of the lithium metal anode was further eliminated after annealing, and the rearrangement of crystal orientation was promoted, resulting in a highly consistent crystal orientation of the obtained lithium metal anode. A comparison between Examples 4 and 10 shows that, at 5 mA / cm 2 ~20mA / cm 2 Within the specified range, increasing the current density improves the uniformity of the lithium deposition crystal planes. A comparison between Example 4 and Example 11 shows that the types of lithium salts and organic solvents in the electrolyte, as well as the content of additives, have a significant impact on the lithium deposition effect.

[0126] In summary, this application combines electrodeposition and roll forming post-treatment. By adding additives to the electrolyte used for electrodeposition and controlling their content, lithium dendrite growth and uneven lithium deposition during high current density electrodeposition are suppressed. Roll forming post-treatment further suppresses lithium deposition on non-{110} crystal planes. Annealing after roll forming eliminates the internal stress of the lithium metal anode, further promoting the preferred orientation growth of the {110} crystal plane. At the same time, the crystal orientation and thickness of the lithium metal anode are controlled by adjusting the current density and deposition capacity. The symmetrical battery assembled using the prepared lithium metal anode material has good cycle performance.

[0127] The applicant declares that the above description is only a specific implementation of this application, but the protection scope of this application is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application fall within the protection and disclosure scope of this application.

Claims

1. A method for preparing a lithium metal anode with preferred crystal orientation, characterized in that, The preparation method includes sequential electrodeposition and rolling post-treatment, wherein the electrolyte used for electrodeposition comprises lithium salt, organic solvent and additives; The additive includes lithium nitrate; The additive is present in the electrolyte at a concentration of 0.05 wt% to 0.5 wt%. The current density of the electrodeposition is 5 mA / cm². 2 above.

2. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (1) Prepare an electrolyte containing lithium salt, organic solvent and additives; (2) In a protective atmosphere, the electrolyte described in step (1) is electrodeposited to deposit lithium metal on the surface of the working electrode to obtain a composite. (3) The composite described in step (2) is subjected to roll pressing post-processing to obtain a lithium metal anode.

3. The preparation method according to claim 2, characterized in that, The lithium salt in the electrolyte in step (1) includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, or lithium bis(fluorosulfonyl)imide. And / or, the lithium salt concentration in the electrolyte of step (1) is 0.5 mol / L to 2.0 mol / L; And / or, the organic solvent in the electrolyte of step (1) includes carbonate solvents and / or ether solvents; And / or, the electrolyte in step (1) may also include auxiliary additives.

4. The preparation method according to claim 3, characterized in that, The carbonate solvent in step (1) includes at least one of ethylene carbonate, diethyl carbonate, or dimethyl carbonate; And / or, the ether solvent in the organic solvent of step (1) includes at least one of 1,3-dioxolane or ethylene glycol dimethyl ether; And / or, the auxiliary additives include cesium hexafluorophosphate; And / or, the content of the auxiliary additive in the electrolyte is 0.01wt%~0.1wt%.

5. The preparation method according to any one of claims 2 to 4, characterized in that, The working electrode in step (2) includes copper foil; And / or, the thickness of the working electrode in step (2) is 6 μm to 20 μm; And / or, the surface roughness Ra of the working electrode in step (2) is less than 1 μm.

6. The preparation method according to any one of claims 2 to 5, characterized in that, The protective atmosphere used in step (2) includes nitrogen and / or an inert gas, wherein the inert gas includes at least one of helium, neon or argon; And / or, the electrodeposition method in step (2) includes constant current electrodeposition; And / or, the deposition capacity of the electrodeposition in step (2) is 2 mA·h / cm 2 ~5mA·h / cm 2 .

7. The preparation method according to any one of claims 2 to 6, characterized in that, The current density for electrodeposition in step (2) is 5 mA / cm². 2 ~20mA / cm 2 .

8. The preparation method according to any one of claims 2 to 7, characterized in that, The post-rolling treatment described in step (3) includes at least one post-rolling treatment; And / or, the rolling temperature of the post-rolling treatment in step (3) is 20℃~40℃; And / or, the rolling speed of the post-rolling treatment in step (3) is 5m / min to 50m / min; And / or, the rolling pressure of the post-rolling treatment in step (3) is 50MPa~200MPa; And / or, after the roll pressing process described in step (3), annealing is performed in an inert atmosphere at a temperature of 60°C to 100°C for a time of 10 min to 60 min.

9. A lithium metal anode with preferred crystal orientation, characterized in that, The lithium metal anode is prepared by the preparation method according to any one of claims 1 to 8; The thickness of the lithium metal anode is 10μm~25μm; The preferred orientation of the lithium metal anode is the {110} crystal plane.

10. A battery, characterized in that, The battery includes a lithium metal anode with preferred crystal orientation prepared by any one of the preparation methods of claims 1 to 8, or includes a lithium metal anode with preferred crystal orientation as described in claim 9.

Citation Information

Patent Citations

  • Electrochemical method for preparing ultrathin lithium metal negative electrode

    CN108346778A

  • Electrochemical preparation method of ultrathin lithium foil and negative pole piece

    CN118888819A